Enfoques da revolução francesa, nazismo e ditadura militar no Brasil: repressão e censura à informação - OLIVEIRA, Alessandra Nunes de (Universidade Federal do Pará, 2018)
Deals with the censorship of the information from three world historical events like the French Revolution which brings the 'attitudes of Illuminists', 'Bücherverbrennung' on Nazism and the 'oppression in literature' in the military dictatorship in Brazil. The objective is to focus on the various forms of censorship applied to documents that were censored in these periods. The methodological approach adopted was accomplished through an exploratory research, bibliographic character based on ideas of authors like Chaffe (2009), Cornelsen (2009), Fioratti (2012) and Darnton (1992), in that approach the historical records, indicating the influence of censorship when it comes to historical facts. The text is finalized integrating historical periods to information, highlighting the importance of information in such historical periods as it opens a new path to democracy. Thus focuses on the intellectual right of access to knowledge through the freedom to search and use information to make up the story and focuses on the contribution of Information Science as an interdisciplinary field of knowledge to the understanding of historical events.